Potential Structuring Forces on a Shelf Edge Upper Mesophotic Coral Ecosystem in the US Virgin Islands - Smith, Tyler B.; Brandtneris, Viktor W.; Canals, Miguel; Brandt, Marilyn E.; Martens, Justin; Brewer, Robert S.; Kadison, Elizabeth; Kammann, Matthew; Keller, Jessica; Holstein, Daniel M. (Frontiers in Marine Science, 2016)
Mesophotic coral ecosystems are extensive light-dependent habitats that typically form between 30 – 150 m depth in the tropical oceans. The forces that structure the benthic communities in these ecosystems are poorly understood but this is rapidly changing with technological advances in technical diving and remote observation that allow large-scale scientific investigation. Recent observations of southeastern Puerto Rican Shelf of the US Virgin Islands have shown that this Caribbean mesophotic coral ecosystem has distinct habitats within the same depth ranges and across small horizontal distances (<<1 km), that range from sparse hardbottom to vibrant coral reefs with stony coral cover >25%. High-resolution bathymetric mapping of the shelf edge revealed a topographically distinct semi-continuous 71 km-long relict barrier reef bank system. The purpose of this study was to characterize the pattern of mesophotic habitat development of the shelf edge and use this data to narrow the potential long-term and large-scale structuring forces of this mesophotic coral ecosystem. We hypothesized from limited preliminary observations that the shelf edge coral cover was limited in shallower portions of the bank and on the seaward orientation. Through stratified random surveys we found that increasing depth and decreasing wave driven benthic orbital velocities were positively related to coral abundance on the shelf edge. In addition, low coral cover habitats of the shelf edge contrasted strongly with adjacent on shelf banks surveyed previously in the same depth range, which had relatively high coral cover (>30%). Predictions of benthic orbital velocities during major storms suggested that mechanical disturbance combined with low rates of coral recovery as a possible mechanism structuring the patterns of coral cover, and these factors could be targets of future research.